2015
DOI: 10.1136/annrheumdis-2015-eular.3167
|View full text |Cite
|
Sign up to set email alerts
|

AB0732 Reliability and Validity of the Duruöz Hand Index in an Argentinian Population with Scleroderma

Abstract: BackgroundThe Duruöz Hand Index (DIH) is a reliable tool for the evaluation of hand's function in patients with scleroderma.ObjectivesThe aim of our study was to adapt and to validate the DHI questionnaire in an Argentinian population with scleroderma.MethodsFor validation, 3 rheumatologists adapted and translated to Spanish the original version in French and the final version was re-translated to French by a bilingual person. To evaluate the construct validity, we used the patient global visual analogue scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gökşenoğlu et al, (2018) and Küçük and Taşkıran, (2020) found that the DHI is valid and reliable tools in patients with CTS. The DHI has been interpreted into a number of languages (Baillet et al, 2009;Duarte et al, 2014;Ingegnoli et al, 2008) and to enable it to be used internationally, it should be translated into local languages and culturally adapted. Therefore, the purpose of this research is to analyze and validate the translated Arabic version of the DHI.…”
Section: Medical Science L Research Articlementioning
confidence: 99%
“…Gökşenoğlu et al, (2018) and Küçük and Taşkıran, (2020) found that the DHI is valid and reliable tools in patients with CTS. The DHI has been interpreted into a number of languages (Baillet et al, 2009;Duarte et al, 2014;Ingegnoli et al, 2008) and to enable it to be used internationally, it should be translated into local languages and culturally adapted. Therefore, the purpose of this research is to analyze and validate the translated Arabic version of the DHI.…”
Section: Medical Science L Research Articlementioning
confidence: 99%